Discovery of a soft X-ray 8 mHz QPO from the accreting millisecond pulsar IGR J00291+5934. Issue 3 (23rd December 2016) - Ferrigno, C.; Bozzo, E.; Sanna, A.; Pintore, F.; Papitto, A.; Riggio, A.; Burderi, L.; Di Salvo, T.; Iaria, R.; D'Aì, A.
Abstract: We report on the analysis of the peculiar X-ray variability displayed by the accreting millisecond X-ray pulsar IGR J00291+5934 in a 80 ks-long joint NuSTAR and XMM–Newton observation performed during the source outburst in 2015. The light curve of the source is characterized by a flaring-like behaviour, with typical rise and decay time-scales of ∼120 s. The flares are accompanied by a remarkable spectral variability, with the X-ray emission being generally softer at the peak of the flares. A strong quasi-periodic oscillation (QPO) is detected at ∼8 mHz in the power spectrum of the source and clearly associated with the flaring-like behaviour. This feature has the strongest power at soft X-rays ( ≲ 3 keV). We carried out a dedicated hardness-ratio-resolved spectral analysis and a QPO phase-resolved spectral analysis, together with an in-depth study of the source-timing properties, to investigate the origin of this behaviour. We suggest that the unusual variability of IGR J00291+5934 observed by XMM–Newton and NuSTAR could be produced by a heartbeat-like mechanism, similar to that observed in black hole X-ray binaries. The possibility that this variability, and the associated QPO, are triggered by phases of quasi-stable nuclear burning, as sustained in the literature for a number of other neutron star binaries displaying a similar behaviour, cannot be solidly tested in the case of IGR J00291+5934 due to the paucity of type I X-ray bursts detected from this source.